WIP: Performance Evaluation of Angle-based Handover in LEO-based NTN - Yu, Jina; Kim, Tae Yoon; Kim, Jae Hyun (Proceedings - 2023 IEEE 24th International Symposium on a World of Wireless, Mobile and Multimedia Networks, WoWMoM 2023, 2023)
Low Earth orbit (LEO) satellite communication is one of the key technologies in 6G wireless networks. However, LEO-based non-terrestrial networks (NTN) face several challenges due to their fast mobility and high altitude. In particular, it is challenging for user equipment (UE) to determine the cell boundary for handover using the received signal strength (RSS)based measurement report (MR) event because the RSS from the cell center and cell edge is quite similar. In this paper, we propose a novel LEO handover method using an angle-based MR event. The elevation angle is calculated based on the distance between the satellite and the cell center, and between the satellite and the UE. Simulation results show that the performance of the angle-based MR event is better than that of the RSS-based MR event.
Keywords: 5g; Cell centers; Earth orbits; Hand over; Low earth orbit; Measurement reports; Received signal strength; Satellite communications; Terrestrial networks; User equipments; 5G; Handover; Low Earth Orbit (LEO); Measurement Report; Satellite Communications